Diversity Of Fishin In Danau Baru, Buluh Cina Village, Siak Hulu Subdistrict, District of Kampar, Riau - Sri Wahyuni; Ridwan Manda Putra; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted in April to June In Danau Baru, Buluh Cina Village, Siak Hulu Sub-district, District of Kampar, Riau. A Fisheries and Aquatic Biology Laboratory Fisheries and Marine Sciene Faculty University of Riau. The purpose of this study is to identify, locate varieties and survey methods by applying 3 sampling stations for fish collection. Identify samples yielded 39 varieties, including the type of the order of 5, 17 genus and 28 familyes. Collected from 39 varieties can be identified that 27 ot them are ornamental fish, 34 species of fish consumed and 8 kinds of fish farming.Key word: Identification, Inventarization, Fish, Danau Baru Oxbow